Pengaruh Intellectual Capital terhadap Kinerja Keuangan Bank Umum Syariah - Nadya Alia; Djoni Djatnika; Destian Arshad Darulmalshah Tamara (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aimss to determine the influence of Intellectual Capital on financial performance (ROA) in the Sharia commercial banking sector in Indonesia. The Independent variables used in this studi are Intellectual capital with the value added human capital, value added capital employed, and structural capital value added, with the control variable for size and leverage. The data type used is secondary data. The results show that Intellectual capital haa a significant negative effect on return on assets. Human capital has a significant positive effect on return on assets, capital employed has a significant negative effect on return on assets, structural capital has a significant positive effect on return on assets, and size has no significant effect on return on assets, leverage has a significant positive effect on return on assets. This study may be useful as an input for Islamic banking practitioners in the management of Intellectual capital in Islamic commercial banks in Indonesia.